DILEMA DETERMINISME MANUSIA: Sebuah Perjalanan Reflektif Sains - Surjani Wonorahardjo (Studia Philosophica et Theologica, 2002)
The development of science and technology cannot be excluded from the human thinking in modern world. One of the major problem which echo comes and goes along the time is the what so called "dilemma of determinism", which is also associated inclusively to the problem of God's existence. Natural science brings a deep implication in thinking leading to determinism of human being as a part of the nature and moves together with the natural processes, that flows according to the natural laws without human decision. But modern science which development is accelerated by the combination of concepts in physics, chemistry and computer, explains that the previous natural laws do not apply in micro systems and the quantum mechanics takes over to rule the behavior of elementary particles in atomic scale. Then modern concepts in science aroused: chaos, complexity, dissipative structure, fractal, which speak about irregularity, unpredictability, then a causality of things that rooted deeply from the microscale dynamics, are expected to be one way out which provides a "chance" which in turn still offers a place for human freedom.